Phonemic transcriptions in British and American dictionaries - Šuštaršič, Rastislav (ELOPE (Ljubljana), 2005)
In view of recent criticisms concerning vowel symbols in some British English dictionaries (in particular by J. Windsor Lewis in JIPA (Windsor Lewis, 2003),with regard to the Oxford Dictionary of Pronunciation (Upton, 2001), this article extends the discussion on English phonemic transcriptions by including those that typically occur in standard American dictionaries, and bycomparing the most common conventions of British and American dictionaries. In addition to symbols for both vowels and consonants, the paper also deals with the different representations of word accentuation and the issue of consistency regarding application of phonemic (systemic, broad), rather than phonetic (allophonic, narrow) transcription. The different transcriptions are assessed from the points of view of their departures from the International Phonetic Alphabet, their overlapping with orthographic representation (spelling) and their appropriateness in terms of reflecting actual pronunciation in standard British and/or American pronunciation.
Keywords: ameriška angleščina; angleščina; britanska angleščina; slovarji; transkripcija